Method for manufacturing clad material
By analyzing the strain energy of aluminum alloy sandwich material and establishing a mathematical model for predicting the thickness of aluminum layer, the problem of small aluminum layer thickness during the rolling bonding process is solved, achieving high accuracy prediction and efficiency improvement of new product development.
Patent Information
- Application Number
- JP2023144884
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
In the manufacturing process of aluminum alloy sandwich materials, the thickness of the aluminum layer is smaller than the design value during the rolling bonding process, and the high accuracy prediction method is lacking, resulting in high cost of new product development and long cycles.
By analyzing the strain energy of aluminum alloy sandwich material during the rolling bonding process, a mathematical model for predicting the thickness of the aluminum layer was established, and the predicted value was calculated using equations 1 and 2, and the total rolling rate of rolling bonding was adjusted to achieve the design thickness goal.
High accuracy prediction of aluminum layer thickness is achieved, reducing design efforts and experimental costs for new product development, and shortening the time for product to go to market.
Smart Images

Figure 2025037758000001 
Figure 2025037758000002 
Figure 2025037758000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for manufacturing a clad material, and more particularly to a method for manufacturing a clad material using an aluminum material. [Background technology]
[0002] Conventionally, known examples of clad materials using aluminum material include a clad material formed by roll-bonding an aluminum material and a copper material (hereinafter referred to as an "Al / Cu clad material") and a clad material formed by roll-bonding an aluminum material and a stainless steel material (hereinafter referred to as an "Al / SUS clad material").
[0003] Al / Cu clad materials are widely used as conductive parts, and have recently been used, for example, in terminals of LIBs (lithium-ion batteries) for vehicles such as HEVs (hybrid electric vehicles) and EVs (electric vehicles) (see Patent Document 1), and conductive members connecting terminals and bus bars (see Patent Document 2).Al / SUS clad materials are also widely used as structural parts that aim to reduce weight while maintaining mechanical strength, and have recently been used, for example, in chassis for smart devices (see Patent Document 3).
[0004] For example, Patent Document 1 discloses an example of a battery terminal made of an Al / Cu clad material. Patent Document 2 discloses an example of a connecting conductive member made of an Al / Cu clad material. Patent Document 3 discloses an example of a composite material made of an Al / SUS clad material in which stainless steel material is roll-bonded to both sides of an aluminum material, and is used as the chassis of a mobile device. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6070490 [Patent Document 2] Patent No. 6071990 [Patent Document 3] Patent No. 7067151 Summary of the Invention [Problem to be solved by the invention]
[0006] Although not disclosed in the above Patent Documents 1 to 3, in clad materials using aluminum material, the thickness ratio of the aluminum material to other metal materials may differ before and after roll joining. This phenomenon of the thickness ratio differing before and after roll joining is considered to be due to the fact that during roll joining, the plastic deformation of the aluminum material proceeds preferentially over other metal materials that have a large equivalent stress for the same equivalent strain. When the above phenomenon occurs, the thickness of the aluminum layer constituting the clad material becomes smaller than the design value (target value), which is undesirable.
[0007] So far, there are no known documents disclosing a method for predicting or forecasting the thickness of the aluminum layer constituting the clad material with high accuracy with respect to the phenomenon that the thickness ratio differs before and after roll bonding observed in clad materials using aluminum materials. Therefore, for clad materials using aluminum materials, it was usually necessary to predict the thickness of the aluminum layer after roll bonding based on manufacturing performance data. However, when developing a new product without manufacturing performance data, it was necessary to find appropriate manufacturing conditions by repeating experiments and prototypes many times. Therefore, in the case of a new product without manufacturing performance data, it was difficult to provide it to the market quickly and cheaply due to the increase in the design man-hours and the cost of experiments and prototypes.
[0008] This invention has been made to solve the above-mentioned problems, and one object of the invention is to provide a method for manufacturing clad materials that introduces a process for predicting with high accuracy the thickness of the aluminum layer after roll bonding, thereby making it possible to reduce design labor and the costs of experimentation and prototyping in the development of new clad materials using aluminum materials. [Means for solving the problem]
[0009] The inventors thoroughly investigated the mechanical properties of clad materials (aluminum materials and other metal materials) and the behavior of clad materials during roll bonding. They then focused on the strain energy of the clad materials during roll bonding and discovered a process for predicting the thickness of the aluminum layer after roll bonding with high accuracy, which led to the invention.
[0010] The method for producing a clad material according to the present invention includes a roll-joining process for forming a clad material having an aluminum layer made of the aluminum material and a high-stress metal layer made of the high-stress metal material by performing roll-joining in a state in which an aluminum material made of aluminum or an aluminum alloy and a high-stress metal material made of a metal having an equivalent stress for an equivalent strain greater than that of the aluminum material are laminated in the thickness direction, and a prediction process for setting a target thickness of the aluminum material and a total rolling ratio of the roll-joining, wherein in the prediction process, an expected thickness of the aluminum material is set as an independent variable t1 Al and the predicted thickness of the aluminum layer is the dependent variable t2 Al As a result, t2 is calculated using Equation 1 and Equation 2. Al If the value is (t2 Al -T2 Al ) / T2 Al t1 satisfies ≦|0.05| Al The value is the target thickness T1 of the aluminum material. Al and the RL value obtained by the formula 3 is set as the total rolling reduction ratio of the roll joining. However, Equation 1: t2 Al =(T2 Al +T2 HS )×B / (B+1) Equation 2: B=t1 Al ×(U Al / U HS ) Equation 3: RL=1-(T2 Al +T2 HS ) / (T1 Al +T1 HS ) and T1 HS : Thickness of highly stressed metal before roll bonding T2 Al : Thickness of aluminum layer after roll bonding T2 HS : Thickness of the highly stressed metal layer after roll bonding U Al : Equivalent strain energy density of aluminum material during roll joining U HS : Equivalent strain energy density of highly stressed metal materials during roll joining It is.
[0011] In the method for producing a clad material according to the present invention, preferably, in the prediction process, t2 calculated by the formula 1 and the formula 2 is Al If the value is (t2 Al -T2 Al ) / T2 Al t1 satisfies ≦|0.03| Al The value is the target thickness T1 of the aluminum material. Al Set as. Effect of the Invention
[0012] According to the present invention, a process is introduced to accurately predict the thickness of the aluminum layer after roll bonding, and a method for manufacturing clad materials can be provided that enables reduction in design labor and experimental / prototype costs in the development of new clad materials using aluminum materials. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, an embodiment of the method for manufacturing a clad material according to the present invention will be described with respect to a clad material using an aluminum material. Note that the method for manufacturing a clad material according to the present invention is not limited to the contents of the embodiment exemplified here, but is indicated by the claims, and includes all modifications within the meaning and scope equivalent to the claims.
[0014] The manufacturing method of the clad material according to the present invention includes a roll-joining process in which an aluminum material (hereinafter simply referred to as "aluminum material") made of aluminum or an aluminum alloy and a high-stress metal material (hereinafter simply referred to as "high-stress metal material") made of a metal having a higher equivalent stress for the same equivalent strain than the aluminum material are stacked in the thickness direction and roll-joined to form a clad material having an aluminum layer made of the aluminum material and a high-stress metal layer made of the high-stress metal material, and a prediction process in which a target thickness of the aluminum material and a total rolling reduction ratio of the roll-joining are set.
[0015] In the method for producing a clad material according to the present invention, in the above prediction process, the estimated thickness of the aluminum material is set as an independent variable t1 Al The predicted thickness of the aluminum layer is the dependent variable t2 Al As a result, t2 is calculated using Equation 1 and Equation 2. Al If the value is (t2 Al -T2 Al ) / T2 Al t1 satisfies ≦|0.05| Al Value of aluminum material target thickness T1 Al and the RL value calculated by the formula 3 is set as the total rolling reduction ratio of the roll joining. In addition, preferably, in the prediction process, t2 calculated by the formula 1 and the formula 2 is set as the total rolling reduction ratio of the roll joining. Al If the value is (t2 Al -T2 Al ) / T2 Al t1 satisfies ≦|0.03| Al The value is the target thickness T1 of the aluminum material. Al Set as.
[0016] However, Equation 1: t2 Al =(T2 Al +T2 HS )×B / (B+1) Equation 2: B=t1 Al ×(U Al / U HS ) Equation 3: RL=1-(T2 Al +T2 HS ) / (T1 Al +T1HS ) and T1 HS : Thickness of highly stressed metal before roll bonding T2 Al : Thickness of aluminum layer after roll bonding T2 HS : Thickness of the highly stressed metal layer after roll bonding U Al : Equivalent strain energy density of aluminum material during roll joining U HS : Equivalent strain energy density of highly stressed metal materials during roll joining It is.
[0017] In the present invention, before the roll-bonding is performed in the roll-bonding process, the thickness of the aluminum layer constituting the clad material after the roll-bonding is predicted in the prediction process by assuming the thickness of the aluminum material before the roll-bonding. Specifically, the assumed thickness of the aluminum material is set as an independent variable t1 Al The predicted thickness of the aluminum layer is the dependent variable t2 Al Let the expected thickness of the aluminum layer be t2 Al Let t1 be the dependent variable when predicting the thickness of the aluminum layer. And let t1 be the independent variable. Al Input value (t1 Al value) according to a specific prediction formula, i.e., Equation 1 and Equation 2 above, the dependent variable t2 Al The output value (t2 Al value).
[0018] And the independent variable t1 Al Enter the dependent variable t2 Al The process of outputting the output value (t2 Al value) satisfies the above specific condition, i.e. (t2 Al -T2 Al ) / T2 Al Repeat until the condition ≦|0.05| is satisfied. As a result, the output value (t2 Al The input value (t1 Al value) to the target thickness T1 of the aluminum material to be prepared for actually forming the clad material.Al Set as.
[0019] In addition, in the above prediction process, the output value (t Al The target thickness T1 of the aluminum material when Al and the thickness of the aluminum layer T2 Al (design value) and the like, the RL value is calculated by the above-mentioned specific calculation formula, that is, by the above-mentioned formula 3. The RL value is set as the total rolling reduction ratio when actually performing roll joining to form the clad material.
[0020] The above-mentioned prediction process allows the desired thickness T2 Al A given target thickness T1 that can form an aluminum layer of (design value) Al It is possible to prepare an aluminum material having a thickness T2 HS A given thickness T1 that allows the formation of a high stress metal layer of (design value) HS Then, in the above-mentioned roll joining process, a high stress metal material having a predetermined target thickness T1 can be prepared. Al of aluminum material and a given thickness T1 HS The high stress metal material is laminated in the thickness direction and roll-joined with a total rolling reduction ratio of RL to form a thickness T2 Al (design value) aluminum layer and high stress metal material thickness T2 HS As a result, the thickness of the aluminum layer that constitutes the clad material (design value T2 Al ) is the expected thickness of the aluminum layer (t Al ) is likely to be easily formed within a range of ±5%.
[0021] In the present invention, the aluminum material for forming the clad material may be appropriately selected from aluminum and aluminum alloys having the desired properties according to the purpose. For example, aluminum alloys such as A3003 and A5052, as well as aluminum such as A1050 and A1100, may be used as the aluminum material.
[0022] In addition, the high stress metal material to be combined with the aluminum material to form the clad material can be appropriately selected by comparing the stress-strain data of candidate metals having the desired properties according to the purpose with the stress-strain data of the appropriately selected aluminum material. Examples of the high stress metal material include oxygen-free copper (C1020, etc.) with a copper content of 99.9% or more, tough pitch copper (C1100, etc.), phosphorus deoxidized copper (C1220, etc.), as well as various stainless steels, nickel, nickel alloys, and other metals.
[0023] In the present invention, the above-mentioned specific prediction formulas, i.e., the above-mentioned formulas 1 and 2, are based on the assumed thickness t1 of the aluminum material before roll bonding. Al Given the expected thickness t2 of the aluminum layer that constitutes the clad material after roll bonding, Al The inventor has devised a method for obtaining the expected thickness t2 of the aluminum layer. Al (t2 Al In the formula 1 for calculating the value of T2 Al (T2 Al T2 is the design value and is the target thickness of the aluminum layer that constitutes the clad material after roll bonding. HS (T2 HS The thickness of the high stress metal layer that constitutes the clad material after roll bonding is a design value.
[0024] Assumed thickness of aluminum material t1 Al (t1 Al In Equation 2, which calculates the B value by giving U Al (U Al The value of U is the equivalent strain energy density of the aluminum material during roll joining. HS (UHS Equation 2 for calculating B (B value) is the equivalent strain energy density of the high stress metal material during roll joining. Al (t1 Al value) and the equivalent strain energy density U of highly stressed metal materials HS (U HS Equivalent strain energy density U of aluminum material for Al (U Al value) (equivalent strain energy density ratio U of aluminum material Al / U HS ) is multiplied by U Al (U Al value) and U HS (U HS The method for calculating the value will be described later.
[0025] In roll joining, a large amount of strain energy is stored in the clad material (aluminum material and high-stress metal material) due to the large deformation caused by rolling. The strain energy stored in the clad material due to the large deformation during rolling is much larger than the energy loss caused by heat generation during rolling, and is stored in the aluminum material and the high-stress metal material according to their respective thicknesses. In this case, the equivalent strain energy stored in the aluminum material is calculated by multiplying the thickness of the aluminum material by the equivalent strain energy density of the aluminum material (t1 Al ×U Al Similarly, the equivalent strain energy stored in the highly stressed metal material during roll joining is the product of the thickness of the highly stressed metal material and the equivalent strain energy density (T HS ×U HS Therefore, the ratio of the equivalent strain energy of aluminum material to that of high stress metal material is (t1 Al ×U Al ) / (T1 HS ×U HS ) The equivalent strain energy stored in the clad material during roll joining is the sum of the equivalent strain energy stored in the aluminum material and the high stress metal material (t1 Al ×U Al +T1 HS ×UHS ) can be obtained.
[0026] However, aluminum materials and high-stress metal materials differ in the ease of plastic deformation due to the rolling load. Due to this difference in the ease of plastic deformation between aluminum materials and high-stress metal materials, the ratio of the equivalent strain energy density of aluminum materials to that of high-stress metal materials (U Al / U HS ) changes, and the ratio of the equivalent strain energy of the aluminum material to that of the high stress metal material also changes. From this point of view, the equivalent strain energy of the aluminum material is calculated by the above product (t Al ×U Al In this case, the equivalent strain energy of the aluminum material is assumed to be t1 Al ×(U Al / U HS ) i.e., the above B value was assumed.
[0027] Here, the ratio of the assumed value of the equivalent strain energy of the aluminum material to the equivalent strain energy of the clad material is called RU. Al As, RU Al =(t1 Al ×U Al ) / (t1 Al ×U Al +T1 HS ×U HS For example, let A be the equivalent strain energy ratio of aluminum material to high stress metal material, and A = (t1 Al ×U Al ) / (T1 HS ×U HS ) Let the formula related to A be (T1 HS ×U HS )=(t1 Al ×U Al ) / A, then RU Al =A / (A+1). On the other hand, the equation related to A is A=t1 Al ×(U Al / U HS )×T1 HS Transform it into the above B=t1 Al×(U Al / U HS ) and A=B×T1 HS Then, B=A / T1 HS The following formula can be derived. Note that B=A / T1 HS This formula is the ratio of the equivalent strain energy (A value) of the aluminum material to the thickness T1 of the high stress metal material. HS The inventors have divided the above-mentioned RU Al =A / (A+1) and the above B=A / T1 HS Focusing on the shape of the clad material, we assumed a term of the form B / (B+1). Then, for B / (B+1), the thickness of the clad material after roll bonding (T2 Al +T2 HS ) to obtain the expected thickness t2 of the aluminum layer that constitutes the clad material after roll bonding. Al We assumed an equation that obtains the above equation 1.
[0028] Next, the above U Al (U Al value) and U HS (U HS This section explains how to calculate the equivalent strain energy density U of aluminum material during roll joining. Al can be obtained based on data showing the relationship between the equivalent stress (σ) and the equivalent strain (ε) of the aluminum material (hereinafter referred to as "stress-strain data"). Similarly, the equivalent strain energy density U of a high-stress metal material during roll joining can be obtained based on data showing the relationship between the equivalent stress (σ) and the equivalent strain (ε) of the aluminum material (hereinafter referred to as "stress-strain data"). HS can be calculated based on the stress-strain data of the high-stress metal material. HS (U HS value) is the U value of aluminum material Al (U Al The U value of aluminum material is calculated in the same way as Al (U Al This will be explained using the case where the value of
[0029] U of the desired aluminum material Al (U AlWhen determining the stress-strain value, the stress-strain data for the aluminum material must be prepared. Stress-strain data for general aluminum materials can be obtained based on the results of tensile tests on aluminum materials conducted in accordance with the metallic material tensile test method specified in JIS-Z2241:2022. If known stress-strain data is available for the desired aluminum material, the known stress-strain data can be used.
[0030] Next, based on the stress-strain data of the desired aluminum material, stress-strain function data is created that expresses the equivalent stress σ as a function of the equivalent strain ε. Then, using this function data, the equivalent stress σ is integrated in the interval from ε1 to ε2 using the equivalent strain ε. The starting point ε1 of the integration interval is the equivalent strain applied to the aluminum material immediately before roll joining is performed. Normally, ε1 = 0. Moreover, the end point ε2 of the integration interval is the equivalent strain applied to the aluminum material during roll joining, and is ε2 = -1 × LN(1-Rp) × (2 / 3 0.5 ) can be calculated. Usually, ε2>ε1. In the above formula for calculating ε2, Rp is the assumed processing rate, and Rp={(t1 Al +T1 HS )-(T2 Al +T2 HS )} / (t1 Al +T1 HS In the above formula for calculating Rp, the denominator (t1 Al +T1 HS ) is the assumed thickness t1 of the aluminum material Al and the thickness T1 of the highly stressed metal material HS (design value or actual measurement value) and is the assumed thickness of the clad material before roll bonding.
[0031] The value obtained by integrating the equivalent stress σ by the equivalent strain ε in the range from ε1 to ε2 based on the stress-strain data of the desired aluminum material using the above-mentioned method is the equivalent strain energy density U of the aluminum material during roll joining. Al (U AlIn addition, the equivalent strain energy density U of the high stress metal material during roll joining is calculated by integrating the equivalent stress σ with the equivalent strain ε in the range from ε1 to ε2 based on the stress-strain data of the desired high stress metal material in the same manner as in the case of the aluminum material described above. HS (U HS value).
[0032] In this invention, the above-mentioned specific prediction formula, i.e., t2 calculated by the above-mentioned formula 1 and formula 2 Al If the value meets the above specific condition, i.e. (t2 Al -T2 Al ) / T2 Al Preferably, (t2 Al -T2 Al ) / T2 Al The assumed thickness t1 of the aluminum material before roll joining is Al Given the expected thickness t2 of the aluminum layer after roll bonding, Al By repeating this trial, t2 Al Appropriate t1 values that satisfy the specific conditions above Al Then, the appropriate t1 value that satisfies the above specific conditions can be obtained. Al Value, target thickness T2 Al The target thickness T1 of the aluminum material to form the aluminum layer Al Set as.
[0033] In the present invention, the RL value calculated by the above specific calculation formula, that is, the above formula 3, is set as the total rolling ratio.
[0034] According to the above-mentioned predicted process, the thickness of the aluminum layer constituting the clad material (design value T2 Al ) is the expected thickness of the aluminum layer (t Al ) and is preferably within ±5% of the expected thickness (t2 Al) is likely to be formed within a range of ±3%. By using the above-mentioned prediction process that involves repeated numerical calculation trials, it is possible to significantly reduce the design man-hours and development costs involved in developing new clad materials that use aluminum materials, compared to the case where repeated experiments and prototype trials are used.
[0035] Below, we will explain the experimental trials using the above-mentioned roll joining process and the prediction trials using the above-mentioned prediction process, which were conducted to confirm the effectiveness of the manufacturing method for clad material using the aluminum material according to the present invention.
[0036] <Experimental Trial> In the experimental trials, the following Experiments 1 to 4 were conducted. In Experiments 1 to 4, roll bonding was actually performed between an aluminum material and a high-stress metal material to produce a clad material having an aluminum layer and a high-stress metal layer. The aluminum material and high-stress metal material shown in Table 1 were prepared as clad materials before roll bonding. In each of Experiments 1 to 4 shown in Table 1, the high-stress metal material has a larger equivalent stress for the same equivalent strain than the aluminum material. In the roll bonding process, Al (Actual measurements) Aluminum material and thickness T1 HS The high stress metal material (actual measurement value) was laminated in the thickness direction and roll-bonded at the total rolling reduction shown in Table 2. Al (Actual measurements) Aluminum layer and thickness T2 HS A clad material shown in Table 2 was formed having a high stress metal layer of (actual measured value).
[0037] [Table 1]
[0038] [Table 2]
[0039] In experiment 1, a clad material was produced with a thickness ratio (design value) of aluminum layer:high stress metal layer = 0.600:0.400. For this purpose, an aluminum material with a thickness of 4.96 mm and a high stress metal material with a thickness of 3.30 mm were prepared, so that the thickness ratio of aluminum material:high stress metal material = 0.600:0.400 was obtained. Then, roll joining was performed using the aluminum material and the high stress metal material. The total rolling ratio during this roll joining was 63.1% (see Table 2). In this case, since the thickness ratio was 0.600, the thickness of the aluminum layer was about 1.83 mm (design value). In contrast, the clad material produced by the above roll joining process had a thickness of 3.05 mm, a thickness of the aluminum layer was 1.67 mm, and a thickness of the high stress metal layer was 1.38 mm. Therefore, the thickness ratio of the aluminum layer:high stress metal layer was 0.548:0.452, and the thickness ratio of the aluminum layer after roll bonding was smaller than the design value by 0.052 (=0.600-0.548).
[0040] In experiment 2, a clad material was produced with a thickness ratio (design value) of aluminum layer:high stress metal layer = 0.566:0.434. To achieve this, an aluminum material with a thickness of 4.30 mm and a high stress metal material with a thickness of 3.30 mm were prepared, so that the thickness ratio of aluminum material:high stress metal material = 0.566:0.434 was obtained. Then, roll joining was performed using the aluminum material and the high stress metal material. The total rolling ratio during this roll joining was 59.9% (see Table 2). In this case, since the thickness ratio was 0.566, the thickness of the aluminum layer was about 1.73 mm (design value). In contrast, the clad material produced by the above roll joining process had a thickness of 3.05 mm, a thickness of the aluminum layer was 1.58 mm, and a thickness of the high stress metal layer was 1.47 mm. Therefore, the thickness ratio of the aluminum layer:high stress metal layer was 0.518:0.482, and the thickness ratio of the aluminum layer after roll bonding was smaller than the design value by 0.048 (=0.566-0.518).
[0041] In experiment 3, a clad material was produced with a thickness ratio (design value) of aluminum layer:high stress metal layer = 0.547:0.453. For this purpose, an aluminum material with a thickness of 3.98 mm and a high stress metal material with a thickness of 3.30 mm were prepared, so that the thickness ratio of aluminum material:high stress metal material = 0.547:0.453 was obtained. Then, roll joining was performed using the aluminum material and the high stress metal material. The total rolling ratio during this roll joining was 58.0% (see Table 2). In this case, since the thickness ratio was 0.547, the thickness of the aluminum layer was about 1.67 mm (design value). In contrast, the clad material produced by the above roll joining process had a thickness of 3.06 mm, a thickness of the aluminum layer was 1.54 mm, and a thickness of the high stress metal layer was 1.52 mm. Therefore, the thickness ratio of the aluminum layer:high stress metal layer was 0.503:0.497, and the thickness ratio of the aluminum layer after roll bonding was smaller than the design value by 0.044 (=0.547-0.503).
[0042] In experiment 4, a clad material was produced with a thickness ratio (design value) of aluminum layer:high stress metal layer = 0.530:0.470. For this purpose, an aluminum material with a thickness of 3.72 mm and a high stress metal material with a thickness of 3.30 mm were prepared, so that the thickness ratio of aluminum material:high stress metal material = 0.530:0.470 was obtained. Then, roll joining was performed using the aluminum material and the high stress metal material. The total rolling ratio during this roll joining was 56.4% (see Table 2). In this case, since the thickness ratio was 0.530, the thickness of the aluminum layer was about 1.62 mm (design value). In contrast, the clad material produced by the above roll joining process had a thickness of 3.06 mm, a thickness of the aluminum layer was 1.49 mm, and a thickness of the high stress metal layer was 1.57 mm. Therefore, the thickness ratio of aluminum layer:high stress metal layer was 0.487:0.513, and the thickness ratio of the aluminum layer after roll bonding was smaller than the design value by 0.043 (=0.530-0.487).
[0043] <Prediction Trial> In the prediction trial, information on the clad material used in the experimental trial was shared, and the experimental and manufacturing predictions described below were made. In the prediction trial, first, the equivalent strain energy density U Al and the equivalent strain energy density U of highly stressed metallic materials HS was calculated based on the respective stress-strain data. Specifically, as shown in Table 3, for Predictions 1 to 4 corresponding to Experiments 1 to 4, the true strain corresponding to the total rolling reduction ratio (see Table 2) during roll joining performed in Experiments 1 to 4 was calculated, and the equivalent strain corresponding to that true strain was calculated. Next, in the stress-strain data of the aluminum material, the start point ε1 of the integral interval was set to zero (ε1 = 0), and the value corresponding to that equivalent strain was set to the end point ε2 of the integral interval, and an integral value was calculated. The integral value was taken as the equivalent strain energy density U of the aluminum material during roll joining. Al Similarly, the equivalent strain energy density U of the high stress metal material during roll joining is HS is an integral value calculated based on the stress-strain data of the high-stress metal material, as in the case of the aluminum material described above.
[0044] [Table 3]
[0045] <Experimental Prediction> Next, the information of the above-mentioned Experiments 1 to 4 was shared, and Experimental Predictions 1 to 4 corresponding to Experiments 1 to 4 were carried out. The results are summarized in Table 4.
[0046] [Table 4]
[0047] In Experiment 1, for the clad material in Experiment 1 above, the thickness of the aluminum material, 4.96 mm (actual measurement value), was used as the independent variable (t1 Al ) and the thickness of the aluminum layer is the dependent variable (t Al) was predicted. The design values (target values) corresponding to Experiment 1 are, as shown in Table 4, a clad material thickness of 3.05 mm, an aluminum layer thickness ratio of 0.600, an aluminum layer thickness of 1.83 mm, and a high stress metal layer thickness of 1.22 mm. The materials used corresponding to Experiment 1 are, as shown in Table 1, an aluminum material with a thickness of 4.96 mm (actual value) and a high stress metal material with a thickness of 3.30 mm (actual value). The equivalent strain energy density is, as shown in Table 3, 112.5 for the aluminum material and 459.9 for the high stress metal material. As a result of the prediction, the predicted thickness of the aluminum layer (t2 Al ) was 1.67 mm, which was the target thickness of the aluminum layer corresponding to experiment 1 (T2 Al ) is smaller than 1.83 mm. The difference (t2 Al -T2 Al ) is -0.16mm. Al -T2 Al ) / T2 Al Since the result is -0.087, the error in this prediction is approximately 8.7%.
[0048] In Experiment 2, for the clad material in Experiment 2, the thickness of the aluminum material, 4.30 mm (actual measurement value), was used as the independent variable (t1 Al ) and the thickness of the aluminum layer is the dependent variable (t Al ) was predicted. The design values (target values) corresponding to experiment 2 are, as shown in Table 4, a clad material thickness of 3.05 mm, an aluminum layer thickness ratio of 0.566, an aluminum layer thickness of 1.73 mm, and a high stress metal layer thickness of 1.32 mm. The materials used for experiment 2 are, as shown in Table 1, an aluminum material with a thickness of 4.30 mm (actual value) and a high stress metal material with a thickness of 3.30 mm (actual value). As shown in Table 3, the equivalent strain energy density is 101.2 for the aluminum material and 404.4 for the high stress metal material. As a result of the prediction, the predicted thickness of the aluminum layer (t2 Al ) was 1.58 mm, which was the target thickness of the aluminum layer for experiment 2 (T2 Al ) is smaller than 1.73 mm. The difference (t2 Al -T2 Al) is -0.15mm. Al -T2 Al ) / T2 Al Since the result is -0.087, the error in this prediction is approximately 8.7%.
[0049] In Experiment 3, for the clad material in Experiment 3, the thickness of the aluminum material, 3.98 mm (actual measurement value), was used as the independent variable (t1 Al ) and the thickness of the aluminum layer is the dependent variable (t Al ) was predicted. The design values (target values) corresponding to experiment 3 are, as shown in Table 4, a clad material thickness of 3.06 mm, an aluminum layer thickness ratio of 0.547, an aluminum layer thickness of 1.67 mm, and a high stress metal layer thickness of 1.39 mm. The materials used in experiment 3 are, as shown in Table 1, an aluminum material with a thickness of 3.98 mm (actual value) and a high stress metal material with a thickness of 3.30 mm (actual value). As shown in Table 3, the equivalent strain energy density is 95.0 for the aluminum material and 374.5 for the high stress metal material. As a result of the prediction, the predicted thickness of the aluminum layer (t2 Al ) was 1.53 mm, which was the target thickness of the aluminum layer corresponding to experiment 3 (T2 Al ) is smaller than 1.67mm. The difference (t2 Al -T2 Al ) is -0.14mm. Al -T2 Al ) / T2 Al Since the result is -0.084, the error in this prediction is approximately 8.4%.
[0050] In Experiment 4, for the clad material in Experiment 4, the thickness of the aluminum material, 3.72 mm (actual measurement value), was used as the independent variable (t1 Al ) and the thickness of the aluminum layer is the dependent variable (t Al) was predicted. The design values (target values) corresponding to experiment 4 are, as shown in Table 4, a clad material thickness of 3.06 mm, an aluminum layer thickness ratio of 0.530, an aluminum layer thickness of 1.62 mm, and a high stress metal layer thickness of 1.44 mm. The materials used for experiment 4 are, as shown in Table 1, an aluminum material with a thickness of 3.72 mm (actual value) and a high stress metal material with a thickness of 3.30 mm (actual value). The equivalent strain energy density is, as shown in Table 3, 90.2 for the aluminum material and 351.6 for the high stress metal material. As a result of the prediction, the predicted thickness of the aluminum layer (t2 Al ) was 1.49 mm, which was the target thickness of the aluminum layer corresponding to experiment 4 (T2 Al ) is smaller than 1.62mm. The difference (t2 Al -T2 Al ) is -0.13 mm. Al -T2 Al ) / T2 Al Since the result is -0.080, the error in this prediction is approximately 8.0%.
[0051] <Production forecast> Next, the information from Experiments 1 to 4 above was shared, and the predicted thickness of the aluminum layer (t Al ) to the target thickness of the aluminum layer (T2 Al ), production predictions 1 to 4 corresponding to Experiments 1 to 4 were carried out.
[0052] <Production forecast 1> In manufacturing forecast 1, as shown in Table 5, the information of the clad material (thickness 3.05 mm) in experiment 1 was shared, and the expected thickness of the aluminum layer (t2 Al In order to bring the thickness ratio of the aluminum layer of 1.83 mm closer to 1.83 mm, manufacturing predictions 1A to 1H were carried out. In addition, in a clad material of 3.05 mm in thickness, the thickness ratio of the aluminum layer of 1.83 mm in thickness is 0.600. As a result of the prediction, as shown in Table 6, the predicted thickness (t Al value) is a specific condition (t2 Al -T2 Al ) / T2 Al Expected thickness (t1 Alvalue), i.e. the appropriate thickness (T1 Al The thickness (T1 Al The appropriate total rolling ratio for roll joining corresponding to the expected thickness (t2 Al value) is a specific condition (t2 Al -T2 Al ) / T2 Al Appropriate thickness (T1 Al The thickness (T1 Al The appropriate total rolling ratio for roll bonding corresponding to the rolling stress (value) was 66.1% to 69.3%.
[0053] From the results of manufacturing forecast 1, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.83 mm ± 5% is formed by performing roll joining with a total rolling ratio of 65.0% to 70.3% corresponding to each aluminum material using aluminum materials with a thickness of 5.42 mm to 6.96 mm. In addition, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.83 mm ± 3% is formed by performing roll joining with a total rolling ratio of 66.1% to 69.3% corresponding to each aluminum material using aluminum materials with a thickness of 5.69 mm to 6.62 mm. In addition, from the results of manufacturing forecast 1E, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.83 mm is formed by performing roll joining with a total rolling ratio of 67.7% using aluminum materials with a thickness of 6.13 mm.
[0054] [Table 5]
[0055] [Table 6]
[0056] <Production forecast 2> In production forecast 2, as shown in Table 7, the information of the clad material (thickness 3.05 mm) in experiment 2 was shared, and the predicted thickness of the aluminum layer (t Al In order to bring the thickness ratio of the aluminum layer of 1.73 mm closer to 1.73 mm, manufacturing predictions 2A to 2H were carried out. In addition, in a clad material of 3.05 mm in thickness, the thickness ratio of the aluminum layer of 1.73 mm in thickness is 0.566. As a result of the prediction, as shown in Table 8, the predicted thickness (t Al value) is a specific condition (t2 Al -T2 Al ) / T2 Al Expected thickness (t1 Al value), i.e. the appropriate thickness (T1 Al The thickness (T1 Al The appropriate total rolling ratio for roll joining corresponding to the expected thickness (t2 Al value) is a specific condition (t2 Al -T2 Al ) / T2 Al Appropriate thickness (T1 Al The thickness (T1 Al The appropriate total rolling reduction ratio for roll bonding corresponding to the tensile strength (value) was 64.1% to 65.8%.
[0057] From the results of manufacturing forecast 2, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.73 mm ± 5% is formed by performing roll joining with a total rolling ratio of 61.7% to 66.8% corresponding to each aluminum material using aluminum materials with a thickness of 4.67 mm to 5.88 mm. In addition, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.73 mm ± 3% is formed by performing roll joining with a total rolling ratio of 64.1% to 65.8% corresponding to each aluminum material using aluminum materials with a thickness of 4.89 mm to 5.62 mm. In addition, from the results of manufacturing forecast 2E, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.73 mm is formed by performing roll joining with a total rolling ratio of 64.3% using aluminum materials with a thickness of 5.24 mm.
[0058] [Table 7]
[0059] [Table 8]
[0060] <Production forecast 3> In production forecast 3, as shown in Table 9, the information of the clad material (thickness 3.06 mm) in experiment 3 was shared, and the predicted thickness of the aluminum layer (t2 Al In order to bring the thickness ratio of the aluminum layer of 1.67 mm closer to 1.67 mm, manufacturing predictions 2A to 2H were carried out. In addition, in a clad material of 3.06 mm in thickness, the thickness ratio of the aluminum layer of 1.67 mm in thickness is 0.547. As a result of the prediction, as shown in Table 10, the predicted thickness (t Al value) is a specific condition (t2 Al -T2 Al ) / T2 Al Expected thickness (t1 Al value), i.e. the appropriate thickness (T1 Al The thickness (T1 Al The appropriate total rolling ratio for roll joining corresponding to the expected thickness (t2 Al value) is a specific condition (t2 Al -T2 Al ) / T2 Al Appropriate thickness (T1 Al The thickness (T1 Al The appropriate total rolling ratio for roll bonding corresponding to the tensile strength (value) was 60.4% to 63.4%.
[0061] From the results of manufacturing prediction 3, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.67 mm ± 5% is formed by performing roll joining with a total rolling reduction rate of 59.5% to 64.4% corresponding to each aluminum material using aluminum materials with a thickness of 4.25 mm to 5.29 mm. In addition, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.67 mm ± 3% is formed by performing roll joining with a total rolling reduction rate of 60.4% to 63.4% corresponding to each aluminum material using aluminum materials with a thickness of 4.70 mm to 5.06 mm. In addition, from the results of manufacturing prediction 3E, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.67 mm is formed by performing roll joining with a total rolling reduction rate of 61.9% using aluminum materials with a thickness of 4.74 mm.
[0062] [Table 9]
[0063] [Table 10]
[0064] <Production Forecast 4> In production forecast 4, as shown in Table 11, the information of the clad material (thickness 3.06 mm) in experiment 4 was shared, and the expected thickness of the aluminum layer (t2 Al In order to bring the thickness ratio of the aluminum layer of 1.62 mm closer to 1.62 mm, manufacturing predictions 2A to 2H were carried out. In addition, in a clad material of 3.06 mm in thickness, the thickness ratio of the aluminum layer of 1.62 mm in thickness is 0.530. As a result of the prediction, as shown in Table 12, the predicted thickness (t Al value) is a specific condition (t2 Al -T2 Al ) / T2 Al Expected thickness (t1 Al value), i.e. the appropriate thickness (T1 Al The thickness (T1 AlThe appropriate total rolling ratio for roll joining corresponding to the expected thickness (t2 Al value) is a specific condition (t2 Al -T2 Al ) / T2 Al Appropriate thickness (T1 Al The thickness (T1 Al The appropriate total rolling ratio for roll bonding corresponding to the tensile strength (value) was 60.1% to 61.6%.
[0065] From the results of manufacturing prediction 4, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.62 mm ± 5% is formed by performing roll joining with a total rolling ratio of 57.8% to 62.5% corresponding to each aluminum material using aluminum materials with a thickness of 3.95 mm to 4.87 mm. In addition, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.62 mm ± 3% is formed by performing roll joining with a total rolling ratio of 60.1% to 61.6% corresponding to each aluminum material using aluminum materials with a thickness of 4.12 mm to 4.67 mm. In addition, from the results of manufacturing prediction 4E, it was found that there is a high possibility that a clad material having an aluminum layer with a thickness of 1.62 mm is formed by performing roll joining with a total rolling ratio of 60.2% using aluminum materials with a thickness of 4.39 mm.
[0066] [Table 11]
[0067] [Table 12]
[0068] From the above, taking into consideration the results of the above-mentioned experimental trials (Experiments 1 to 4) and predicted trials (experimental prediction, manufacturing prediction), the effectiveness of the manufacturing method of the clad material using the aluminum material according to the present invention can be confirmed. Therefore, by applying the present invention, it becomes possible to predict the thickness of the aluminum layer after roll bonding with high accuracy, so that it is possible to provide a manufacturing method of the clad material that enables reduction in the design man-hours and the costs of experiments and prototypes in the development of new clad materials using aluminum materials.
Claims
1. a roll-bonding process for forming a clad material having an aluminum layer made of the aluminum material and a high-stress metal layer made of the high-stress metal material by stacking an aluminum material made of aluminum or an aluminum alloy and a high-stress metal material made of a metal having a higher equivalent stress for an equivalent strain than the aluminum material in a thickness direction and performing roll-bonding in that state; A prediction process for setting a target thickness of the aluminum material and a total rolling reduction of the roll bonding, In the prediction process, the assumed thickness of the aluminum material is defined as an independent variable t1 Al and the predicted thickness of the aluminum layer is the dependent variable t2 Al t2 calculated by Equation 1 and Equation 2 Al The value is (t2 Al -T2 Al ) / T2 Al t1 that satisfies ≦|0.05| Al The value is the target thickness T1 of the aluminum material. Al and the RL value calculated by the formula 3 is set as the total rolling ratio of the roll joining. However, Formula 1: t2 Al = (T2 Al +T2 HS ) × B / (B + 1) Formula 2: B = t1 Al × (U Al / U HS ) Formula 3: RL = 1-(T2 Al +T2 HS ) / (T1 Al +T1 HS ) and T1 HS : Thickness of highly stressed metal material before roll bonding T2 Al : Thickness of aluminum layer after roll bonding T2 HS : Thickness of the highly stressed metal layer after roll bonding U Al : Equivalent strain energy density of aluminum material during roll joining U HS : Equivalent strain energy density of highly stressed metal materials during roll joining It is.
2. In the prediction process, t2 calculated by Equation 1 and Equation 2 Al The value is (t2 Al -T2 Al ) / T2 Al t1 that satisfies ≦|0.03| Al The value is the target thickness T1 of the aluminum material. Al A method for manufacturing a clad material using the aluminum material according to claim 1, wherein
Citation Information
Patent Citations
Discharge lamp lighting apparatus
JP1985070490A
Reactor containing vessel
JP1985071990A
Clad and metal composites
JP7067151B2